Analisis implementasi internal control dalam sistem akuntansi piutang - Sukmahadi, Sukmahadi; Nurfarizah, Resa Sifa (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This reasearch implementation the internal control account receivables. accounting system is a system that handles transactions related to receivables. Receivables in the balance sheet are an important element and require good policy from management in its management. The research studied in this study is handling how the accounting system of receivables from KPRI SADAR Pangalengan which includes what are the related functions, what are the documents used, what accounting records are used and how to control the internal. The purpose of this research is to find out the related functions, documents used, accounting records used, procedures that form the receivables accounting system as well as internal control in the receivables accounting system. The results of the study can be concluded that the accounting system of receivables in KPRI SADAR Pangalengan is good enough but there are weaknesses in the procedure which has not involved the function of receivables to help smooth recording of receivables.